The problem of implementation of imperial veterinarian practices into the system of Kazakh animal husbandry: primary sources analyses (Journal of history, 2021)
The article analyzes the complex of collected sources to study the problem of the formation anddevelopment of the veterinary service system in the Turgai region, as a colonial project, towards theimplementation of pragmatic goals. The sources represent workflow documents (deloproizvodstvennyedokumenty), materials of statistical and research expeditions of the second half of the nineteenthcentury, a number of scientific and publicistic publications, and scientific works of the conductors ofimperial politics, folklore and ethnographic sources, which are classified and divided into several groups.Due to the systematization of sources, according to the type of production and inherent vision, they wereconditionally divided into two corpuses of different worldviews. Sources divided to the correspondingprinciple were classified and developed for each group of sources general principles of work, and, dependingon the purpose, ideology and subject matter of the sources, were subdivided into types. Thesystematization and classification of these types were supplemented by an analysis of semantic meanings,genre specificity of sources, which study the reasons, patterns and their changes. Thus, in turn, willallow, using new methods of source analysis, to comprehensively investigate the problem of the formationand development of the veterinary service in the steppe, which brought about the transformation ofthe traditional economy of the Kazakhs.Key words: workflow documents (deloproizvodstvennye dokumenty), materials of expeditions, scientificworks, folklore, ethnographic sources, the system of veterinary service, transformation, Turgairegion.